Conformational control over an aldehyde fragment by selective vibrational excitation of interchangeable remote antennas. Issue 38 (13th April 2018) - Lopes Jesus, A. J.; M. Nunes, Cláudio; Fausto, Rui; Reva, Igor
Abstract : We apply vibrational antennas (OH or NH2 group) to achieve unprecedented conformational control over the heavy aldehyde fragment in 2-formyl-2 H -azirine, using selective vibrational excitations of the OH or NH2 stretching overtones and combination modes. Abstract : We apply interchangeable vibrational antennas (OH or NH2 group) to achieve unprecedented conformational control over the heavy aldehyde fragment in 2-formyl-2 H -azirine. The two aldehyde conformers were manipulated bi-directionally, using selective vibrational excitation with narrowband near-infrared (NIR) light tuned at the wavenumbers corresponding to OH and NH2 stretching overtones and combination modes.